HYPOKALEMIA IN ACUTE MESENTERIC ISCHEMIA IN CHRONIC SMOKER - SHANTHI; MANJULADEVI; RAJINI SAMUEL (International Journal of Pharma and Bio Sciences, 2014)
Ischemic enteritis is a disease of the elderly, with more than 90% of the cases occurring during the age 60. Ischemic enteritis is difficult to estimate as many patients with mild ischemia may not seek medical attention. It is also important to differentiate ischemic colitis, which often resolve on its own from the more immediately life threatening condition of acute mesenteric ischemia of the small bowel. Here, we presented a case in which 49 yr / male with H/O chronic heavy smoker ( more than 25 yrs ) came to casualty with acute pain abdomen with hypokalemia and leukocytosis and the patient was taken for laporotomy and resection of the gangrenous bowel was done.